The MANGOSTEEN FARMING DEVELOPMENT MODEL (Garcinia Mangostana) IN KERINCI REGENCY - Effran, Endy; Saputra, Ardhiyan (Universitas Jambi, 2024)
This study aims to 1). Describing mangosteen farming in Keliling Danau District, Kerinci Regency. 2). Identify internal and external factors of mangosteen farming development in Kerinci Regency Keliling Danau District. 3). Formulate alternative mangosteen farming development strategies in Keliling Danau District, Kerinci Regency. This research was conducted for 2 months in Keliling Danau District with 52 farmers. The data used are primary data and secondary data. The data was analyzed using descriptive methods and SWOT approaches (Strenght, Weakness, Opportunities, Threats). The results showed that mangosteen farming is cultivated on hilly land with very limited cultivation techniques without touch and use of technology, there are internal factors consisting of seven strengths and four weaknesses, while external factors consist of six opportunity factors and five threat factors. The results of the SWOT matrix analysis, that the development of mangosteen farming in Keliling Danau District is in quadrant I or aggressive strategy. The mangosteen farming development strategy in Keliling Danau District that can be used is the SO strategy, utilizing its strengths optimally and utilizing existing opportunities. Increase the amount of mangosteen production in order to meet market demand.